(untitled) - Dickens, Charles (Đồng Nai, 2009)
'Please, Mr Murdstone! Don't beat me! I've tried to learn my lessons, really I have, sir!' sobs David. Although he is only eight years old, Mr Murdstone does beat him, and David is so frightened that he bites his cruel stepfather's hand. For that, he is kept locked in his room for five days and nights, and nobody is allowed to speak to him. As David grows up, he learns that life is full of trouble and misery and cruelty. But he also finds laughter and kindness, trust and friendship ...and love.
Keywords: English language,Ngôn ngữ tiếng Anh,Novels,Tiểu thuyết; Readers,Người thích đọc sách